Concurrent tolerance allocation and scheduling for complex assemblies. (October 2015) - Geetha, K.; Ravindran, D.; Kumar, M. Siva; Islam, M.N.
Abstract: Traditionally, tolerance allocation and scheduling have been dealt with separately in the literature. The aim of tolerance allocation is to minimize the tolerance cost. When scheduling the sequence of product operations, the goal is to minimize the makespan, mean flow time, machine idle time, and machine idle time cost. Calculations of manufacturing costs derived separately using tolerance allocation and scheduling separately will not be accurate. Hence, in this work, component tolerance was allocated by minimizing both the manufacturing cost (sum of the tolerance and quality loss cost) and the machine idle time cost, considering the product sequence. A genetic algorithm (GA) was developed for allocating the tolerance of the components and determining the best product sequence of the scheduling. To illustrate the effectiveness of the proposed method, the results are compared with those obtained with existing wheel mounting assembly discussed in the literature. Highlights: Tolerance allocated based on manufacturing and machine idle time cost with product sequence. Tolerance allocation and the best product sequence in scheduling have determined using GA